2020
DOI: 10.1038/s41467-020-14840-w
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric population sensing by a pump-probe signaling system in Bacillus subtilis

Abstract: Communication by means of diffusible signaling molecules facilitates higher-level organization of cellular populations. Gram-positive bacteria frequently use signaling peptides, which are either detected at the cell surface or 'probed' by intracellular receptors after being pumped into the cytoplasm. While the former type is used to monitor cell density, the functions of pump-probe networks are less clear. Here we show that pump-probe networks can, in principle, perform different tasks and mediate quorum-sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 69 publications
0
23
0
1
Order By: Relevance
“…Ratiometric sensing was recently described for other binary populations, such as those composed of signal producers and signal “cheaters” in the PhrA-RapA-Spo0F signaling pathway in Bacillus subtilis [ 26 ] and yeast mating types [ 24 ]. In both cases, ratiometric sensing is achieved by cell density–dependent reductions in extracellular signal availability.…”
Section: Discussionmentioning
confidence: 99%
“…Ratiometric sensing was recently described for other binary populations, such as those composed of signal producers and signal “cheaters” in the PhrA-RapA-Spo0F signaling pathway in Bacillus subtilis [ 26 ] and yeast mating types [ 24 ]. In both cases, ratiometric sensing is achieved by cell density–dependent reductions in extracellular signal availability.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, every cell produces signaling molecules, shares signaling molecules, and coordinately responds to the signaling molecules. In recent years, however, it was shown that the expression of signaling molecules can be heterogenous [23][24][25][26] . When the concentration of signaling molecule reaches a threshold value, a coordinated and homogeneous expression of target genes may be initiated in all cells of the population 5,27 or a heterogeneous gene expression in the population may be triggered at low concentrations 25,27,28 .…”
mentioning
confidence: 99%
“…Based on comparison of the sizes and integration sites of prophage elements within Bacillus sp., SPβ and phi3T clearly belong to a distinct prophage group. These phages appear extremely large (2-3-fold larger than average prophages), and they possess sophisticated communication systems that are potentially capable of sensing the frequency of lysogenized hosts [64, 87] or biosynthetic gene clusters [88, 89], and functional genes related to host dormancy [90, 91]. A high level of homology between SPβ and phi3Ts offers extensive regions for homologous recombination, which can be additionally promoted by the recombination machinery involved in natural competence [92] and in non-homologous end-joining repair [93].…”
Section: Discussionmentioning
confidence: 99%